2014
DOI: 10.4148/2378-5977.6912
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a novel protease enzyme (CIBENZA DP100) on finishing pig growth performance and carcass characteristics (2014)

Abstract: Effects of a novel protease enzyme (CIBENZA DP100) on finishing pig growth Effects of a novel protease enzyme (CIBENZA DP100) on finishing pig growth performance and carcass characteristics performance and carcass characteristics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In addition, there were no differences on carcass characteristics among dietary treatments (Table 4). These results were similar to the results of previous studies [16,28,29], but Wang et al [30] showed addition of dietary protease in the pig diet changed carcass characteristics of pigs. However, further investigation is needed to clarify the effects of dietary protease on the blood constituents and carcass characteristics of growing-finishing pigs.…”
Section: Resultssupporting
confidence: 91%
“…In addition, there were no differences on carcass characteristics among dietary treatments (Table 4). These results were similar to the results of previous studies [16,28,29], but Wang et al [30] showed addition of dietary protease in the pig diet changed carcass characteristics of pigs. However, further investigation is needed to clarify the effects of dietary protease on the blood constituents and carcass characteristics of growing-finishing pigs.…”
Section: Resultssupporting
confidence: 91%
“…There were no significant differences between treatments on carcass characteristics of pigs by addition of PRO in the pig diets (Table 4). Similar results were observed in previous studies [20,21,35], but other previous work did show changed of carcass characteristics of pigs when PRO was added in the diets [35,36]. The inconsistent results may be due to different type of PRO used and the conditions and stages of pig age when PRO were added into the diets.…”
Section: Absupporting
confidence: 87%
“…Until now, the effect of different proteases on pigs is still controversial [ 15 , 16 , 17 ]. Angel et al [ 18 ] and Freitas et al [ 19 ] showed that the beneficial effect of protease increased with the increase in protease dose in a linear [ 18 ] or quadratic [ 19 ] manner.…”
Section: Introductionmentioning
confidence: 99%